2020
DOI: 10.32383/appdr/115158
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium rutin complex sensitizes breast cancer cells via modulation of p53/Bax/Bcl2/VEGF correlated with apoptotic events

Abstract: In pursuit of a novel approach in breast cancer therapy, we explored the ability of vanadium-rutin complex to eradicate cancer by efficiently targeting various apoptotic pathways on human breast cancer cell lines. We provide direct proof of the chemotherapeutic potential of the vanadium-rutin complex by activating p-53 dependent intrinsic apoptosis and modulating the VEGF pathways. The complex was also capable of binding and cleaving CT-DNA at different concentrations. The complex was able to inhibit cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Specifically, rutin increased GSH level and activities of antioxidant enzymes (catalase, glutathione peroxidase, and superoxide dismutase), as well as decreased malondialdehyde level ( Caglayan et al, 2019 ). As it has been demonstrated that rutin was not only able to induce pro-apoptotic effect in cancer cells via similar mechanisms as tHGA ( Iriti et al, 2017 ; Hasani et al, 2018 ; Saleh et al, 2018 ; Kunjiappan et al, 2019 ; Haifeng et al, 2020 ), but also capable of inhibiting xenobiotic-induced apoptosis in normal cells ( Caglayan et al, 2019 ), therefore it is probable that tHGA may be able to suppress xenobiotic-induced apoptosis in normal cells as well. As such, it would be worthwhile to investigate the effect of tHGA on xenobiotic-induced apoptosis in normal cells for future studies.…”
Section: The Way Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, rutin increased GSH level and activities of antioxidant enzymes (catalase, glutathione peroxidase, and superoxide dismutase), as well as decreased malondialdehyde level ( Caglayan et al, 2019 ). As it has been demonstrated that rutin was not only able to induce pro-apoptotic effect in cancer cells via similar mechanisms as tHGA ( Iriti et al, 2017 ; Hasani et al, 2018 ; Saleh et al, 2018 ; Kunjiappan et al, 2019 ; Haifeng et al, 2020 ), but also capable of inhibiting xenobiotic-induced apoptosis in normal cells ( Caglayan et al, 2019 ), therefore it is probable that tHGA may be able to suppress xenobiotic-induced apoptosis in normal cells as well. As such, it would be worthwhile to investigate the effect of tHGA on xenobiotic-induced apoptosis in normal cells for future studies.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Rutin, a bioactive plant flavonoid and natural antioxidant, has been well reported to induce apoptosis in various cancer cells including MCF-7 human breast cancer cells (Iriti et al, 2017;Hasani et al, 2018;Saleh et al, 2018;Kunjiappan et al, 2019;Haifeng et al, 2020). Similar to tHGA, rutin exhibited its pro-apoptotic effect in MCF-7 cells by increasing Bax expression, GSH level, caspase cascade activation and chemosensitivity, as well as decreasing Bcl-2 expression (Iriti et al, 2017;Hasani et al, 2018;Saleh et al, 2018;Kunjiappan et al, 2019;Haifeng et al, 2020). However, in contrast to tHGA, rutin was capable of inhibiting mercury-induced apoptosis in normal cells (Caglayan et al, 2019).…”
Section: The Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation